Shortcomings and inadequacies of autonomy argument for euthanasia - Malik, Mohammad Manzoor (Bangladesh Bioethics Society (BBS), 2014)
Patient autonomy has a critical role in making decisions in medical practice and it is accepted by international conventions on health care and various national medical codes. However, pertaining to terminally ill patients, this right becomes very problematic in regards to end of life decisions. Utilitarian ethicists motivated by materialistic worldview and individualism have made patient autonomy based arguments for the permissibility of active euthanasia. An appraisal of pro-euthanasia arguments that include the best interest, golden rule, and autonomy is made in this paper. The best interest and golden rule arguments are based on subjective moral judgment thus failing the universalization test. The argument from autonomy is unconvincing because of the confounded autonomy of the terminally ill patients.